Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1365-2141.2004.05188.x
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of two doses of bortezomib in relapsed or refractory myeloma

Abstract: Summary In a phase 2 open‐label study of the novel proteasome inhibitor bortezomib, 54 patients with multiple myeloma who had relapsed after or were refractory to frontline therapy were randomized to receive intravenous 1·0 or 1·3 mg/m2 bortezomib twice weekly for 2 weeks, every 3 weeks for a maximum of eight cycles. Dexamethasone was permitted in patients with progressive or stable disease after two or four cycles respectively. Responses were determined using modified European Group for Blood and Marrow Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
509
7
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 649 publications
(568 citation statements)
references
References 13 publications
38
509
7
14
Order By: Relevance
“…Although we used 1.0 mg/m 2 of bortezomib in our VRD regimen, the incidence of grade 3/4 peripheral neuropathy was similar with that observed with the dose of 1.3 mg/m 2 of bortezomib in other studies with bortezomib-based regimens 10,37 and higher than that observed with the same dosage of bortezomib-1.0 mg/m 2 in CREST trial (the incidence of peripheral neuropathy was 8%). 37 This may be due to the difference in study population and/or due to the presence of lenalidomide, which can produce severe peripheral neuropathy in 3% of MM patients when it is given as monotherapy 38 and in o1% when it is given in combination with dexamethasone 1 in the relapsed/refractory setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although we used 1.0 mg/m 2 of bortezomib in our VRD regimen, the incidence of grade 3/4 peripheral neuropathy was similar with that observed with the dose of 1.3 mg/m 2 of bortezomib in other studies with bortezomib-based regimens 10,37 and higher than that observed with the same dosage of bortezomib-1.0 mg/m 2 in CREST trial (the incidence of peripheral neuropathy was 8%). 37 This may be due to the difference in study population and/or due to the presence of lenalidomide, which can produce severe peripheral neuropathy in 3% of MM patients when it is given as monotherapy 38 and in o1% when it is given in combination with dexamethasone 1 in the relapsed/refractory setting.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical evidence provides a rationale for combining bortezomib with dexamethasone, suggesting that the effects of these two agents could be additive and that bortezomib may overcome resistance of MM cell lines to dexamethasone [27]. In two previous trials, bortezomib (1.0 or 1.3 mg/m 2 ) was administered intravenously twice weekly for 2 weeks of a 3-week cycle for up to 8 cycles to patients who had failed second line therapy [10,11,28]. In these trials, patients with progressive disease after two cycles or stable disease after four cycles of bortezomib were eligible for addition of oral dexamethasone (20 mg) on the day of and after each bortezomib dose.…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib has been demonstrated to be an effective option for MM patients with advanced disease [9][10][11][12][13][14]. However, available published studies included a mixture of patients with multiple and heterogeneous previous regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In phase 1-2 studies [9][10][11], as well as in community centers compassionate need programs [12,13] bortezomib was effective as single agent in 35-38% (and up to 50%, when dexametasone was added) of patients with advanced MM. In a recently published phase 3 trial, bortezomib did significantly better than dexamethasone as salvage treatment in MM in terms of response rate, time to progression and survival benefits [14].…”
Section: Introductionmentioning
confidence: 99%